Systems for Drug Delivery Safety, Animal, and Microbial Polysaccharides - Bhatia, Saurabh (Springer International Publishing : Imprint: Springer, 2016)
This book details current developments in all natural polymers, with a focus on animal and microbial polysaccharides. The book examines, compares, and contrasts the efficiency of plant and algae based natural polymers in inducing immune reactions. Additionally, the book details the safety and toxicity profiles with respective regulations.